2020
DOI: 10.5603/demj.a2020.0032
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Emergency Ultrasonography in Non-Traumatic Cardiac Arrest and Near-Arrest Emergency Patients; A Pilot Trial

Abstract: INTRODUCTION: In this study, we evaluated the applicability and interpretation of point-of-care emergency ultrasound (POCEUS) performed by an emergency physician (EP) in non-traumatic adult cardiac arrest and near-arrest patients at presentation to the Emergency Department (ED). METHODs: POCEUS was performed in 5 steps on 73 adults to assess; 1. Qualitative global cardiac function, cardiac chambers and presence of pericardial effusion; 2. Presence of pleural sliding, B-lines, A-lines or consolidation on anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The second most useful application of echocardiography during CPR is that of determining the probability of a successful resuscitation. In this situation echocardiography is used to identify spontaneous cardiac movement [ 11 , 12 ]. The meta-analysis conducted by Tsou et al [ 11 ] has revealed that spontaneous cardiac movement possesses a sensitivity and specificity of 95% and 80% (95% confidence interval [CI] 0.72–0.99, and 0.63–0.91, respectively) for predicting return of spontaneous circulation (ROSC) during cardiac arrest, with a positive and negative likelihood ratio of 4.8 and 0.06 (95% CI 2.5–9.4, and 0.01–0.39, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The second most useful application of echocardiography during CPR is that of determining the probability of a successful resuscitation. In this situation echocardiography is used to identify spontaneous cardiac movement [ 11 , 12 ]. The meta-analysis conducted by Tsou et al [ 11 ] has revealed that spontaneous cardiac movement possesses a sensitivity and specificity of 95% and 80% (95% confidence interval [CI] 0.72–0.99, and 0.63–0.91, respectively) for predicting return of spontaneous circulation (ROSC) during cardiac arrest, with a positive and negative likelihood ratio of 4.8 and 0.06 (95% CI 2.5–9.4, and 0.01–0.39, respectively).…”
Section: Introductionmentioning
confidence: 99%